Pencapaian Kinerja Melalui Responsifitas Pada Pesaing Dengan Moderasi Tensi Persaingan Dan Kelonggaran Sumberdaya - Muslich Anshori; Badri Munir Sukoco; Mikhael Mangihot Napitupulu (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
Telecommunication industry in Indonesia is growing rapidly in the last two decades. Prepaid services remain dominant (above 90%), in which 95% are distributed electronically. The condition attracts many players to participate in the business and eventually increasing the competitive tension among them. Based on market orientation perspective, we investigate whether responsiveness toward competitors deliver higher performance for electronic server company? Moreover, this study address under which conditions that the relationship is strengthened or weakened? By distributing questionnaires among all electronic server companies in Surabaya, we reported that responsiveness toward competitors positively contribute to companies’ performance. The relationship strengthened when the slack resources was low than high, while there was no moderating effect of competitive tension. Managerial and academic implications are further discussed.